Appearance of F-wave during electrophysiological study of - E. Sulaiman, Mohammed (Tikrit Journal of Pharmaceutical Sciences, 2023)
To evaluate the appearance of F-wave in patients with carpal tunnel syndrome through electrophysiological study. Fifty patients with carpal tunnel syndrome(CTS) of the median nerve who were diagnosed clinically and through electrophysiological study for median and ulnar nerve. Fifty normal subjects of healthy volunteers of similar age and gender were compared to the patients and examined for nerve conduction study. Nerve conduction study for median and ulnar nerve (motor and sensory) were done for each patient and subject in neurophysiology department to study the distal motor and sensory latency (DML,DSL), compound motor and sensory action potentials (CMAP,SNAP) ,motor and sensory nerve conduction velocities (MNCV,SNCV) and F-wave latencies(maximum, mean and minimum). There are prolonged distal motor and sensory latency, decrease of compound motor and sensory action potential, decrease of motor and sensory nerve conduction velocity and prolongation of F-wave latencies( minimum, mean and maximum.) of the median nerve (motor) in carpal tunnel syndrome patients compared with the controls and these differences are statistically significant p-value < 0.01. The F-wave parameters for median nerve must be added in electrophysiological study to establish the diagnosis of carpal tunnel syndrome.